Avaliação da estratégia saúde da família a partir das crenças de seus profissionais - Melo, Cynthia de Freitas (2009)
From the decree 648/06 the Family Health Strategy (ESF) becomes seen as a structuring strategy of Basic Care. In this scenario, the evaluation researches of ESF work as a fundamental tool to help, through feedback, the decisions of its managers. Systematic information that can be used in the improvement of governmental actions. Professionals, who are the implementers of these actions, become valuable source of information, because in addition to knowing the reality of everyday ESF, they are also subjects that have the power to change it. This way, this study aimed to evaluate the Family Health Strategy (ESF) in João Pessoa, Paraíba, from the beliefs of professionals in the Health Team Family (EqSF), in order to understand the factors that influence the effective performance of work of these teams in the ESF, enabling its success or failure. It has been done a descriptive correlational applied research, in which the antecedent variables relate to working conditions in the Unities of the Family Health (USF) and professionals profile, and consequent variables are the beliefs that professionals of EqSFs have on the strategy. It has been used probability sample composed by 337 professionals of EqSF. For data collection, it was created and validated the Evaluation Scale of ESF by Professionals with 24 items and four points in response. Investigates the following factors: 1) Material resources (α = 0.86), with 10 items, 2) Efficiency in assistance (α= 0.80), with 8 items, 3) Physical Infrastructure (α = 0.73 ), with 6 items, which was answered by an individual configuration in the 101 USFs where professionals sorted to the samples work. Data analysis took place in five phases: in the first, it has been done exploratory analysis, aiming to clear the bank, and identify possible digitation errors. Next, it has been done a factor analysis of the Scale for the Evaluation of the Family Health Strategy (ESF), to verify the adequacy of items to factors. In the third stage it has been used descriptive statistics (frequency, percentage, mean, standard deviation) in Bio-demographic data to provide information about the sample. Subsequently, it has been made means and standard deviations of the items of the scales to check the scores of the factors. It has even been made frequencies and percentages for each item of factors. Finally, comparisons were made between professionals by education (high school and technical versus higher), by T Student test and chi-square, and by professional category, by ANOVA. Overall, the results showed distinctions in types of employment contracts for professionals. It was found that the average stay of these professionals in USFs, is 3.9 years (SD = 2.60). And each EqSF is responsible for an average of 946.49 families (SD = 200). The monthly rents range from 400 reais to 7,000 reais and 13.1% of professionals say they have another job. With regard to the evaluation that the professionals do to the ESF, the availability of material resources obtained a positive evaluation by 76.68% of the professionals. The efficiency of care was rated negatively by 53.4% of participants. And the infrastructure of USF was evaluated positively by 71.17% of the professionals. Observing, however, some caveats to camouflage the positive evaluations. It was even verified that the material resources and infrastructure of USFs were better rated by professionals of superior level. And the efficiency in assistance was better rated by professionals of medium/technical level. It was concluded that, despite limitations, the ESF in Joao Pessoa was evaluated positively by their professionals, presenting significant advances in the reality of operation.